Illocutionary Force in The Novel Darkest Hour By Cleo Virginia Andrews - Wilda Mahya Sari; Lidiman Sahat Martua Sinaga (LINGUISTICA, 2013)
ABSTRACT One aim of this article is to show through concrete examples about how Illocutionary Force used in Novel Darkest Hour By Cleo Virginia Andrews. The research are to describe the six types of illocutionary force in Cleo Virginia Andrews’s Darkest Hour to derive the most dominant type of illocutionary force, to explain the meaning of illocutionary force and to analyze the implication of that dominant the six types of illocutionary force to the novel itself. This study applied descriptive qualitative method.  They were taken randomly and found 108 the types of illocutionary force; Asserting   (21,29 %), Promising  (13,89 %), Excomunicating ( 12,04%), Exclaiming in pain (15,74 %), Inquiring (11,11 %), and Ordering (25,92%) occurs in the novel. It was found that the most dominant type of illocutionary force that is used in Cleo Virginia Andrews’s Darkest Hour is Ordering for expressing what the speaker wants (25,92%).  This implies that the Ordering for expressing what the speaker wants play a great role in the novel. It means that wishes as expression of speaker’s desire or wants in order to expect it becomes    a reality can be characteristic of the novel in case of applying order to express of Illocutionary Force within utterances. Keywords: Illocutionary Force, Novel Darkest Hour By Cleo Virginia Andrews, documentary, descriptive qualitative